2016
DOI: 10.1108/jfc-03-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Rana disaster: how far can we proceed with CSR?

Abstract: Purpose This paper aims to investigate corporate social responsibility (CSR) in corporate business and stimulate a debate on this to combat the modern day slavery in Garment Industries (GIS) in Bangladesh. Design/methodology/approach This research has drawn on media, non-governmental organisations and a series of national and international reports and on relevant materials from both primary and secondary legal resources. Findings The existing phenomena in Bangladesh surrounding Rana Plaza (RP) disaster sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The collapse of the Rana Plaza in Savar Upazila, Dhaka, Bangladesh on 24 April 2013, was the worst and deadliest garment factory disaster on record [1,2]. More than 1100 workers were killed, approximately 2500 injured, and about 100 left missing among the 5000 workers in the various factories located at the Rana Plaza on that day [3,4,5,6,7,8,9,10,11]. The collapse of the eight-story building, which housed a private bank, apartments, stores, and clothing factories, occurred the day after the discovery of a crack on the third floor [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The collapse of the Rana Plaza in Savar Upazila, Dhaka, Bangladesh on 24 April 2013, was the worst and deadliest garment factory disaster on record [1,2]. More than 1100 workers were killed, approximately 2500 injured, and about 100 left missing among the 5000 workers in the various factories located at the Rana Plaza on that day [3,4,5,6,7,8,9,10,11]. The collapse of the eight-story building, which housed a private bank, apartments, stores, and clothing factories, occurred the day after the discovery of a crack on the third floor [1].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to Rana Plaza, the owner of the factory building was illegally given permission by the local municipality to construct additional floors and construction work was underway to add floors to the top of the building at the time of the collapse [13,20], resulting in weakening of the overall structure. Since the collapse and associated investigations as to the cause of the collapse, it has been reported that the government was found to have failed in applying building codes and regular inspections [9,18,19,20,21] to the site. In addition, underlying corruption was found to have influenced government approvals due to the strong affiliations between the RMG owners and political powers in Bangladesh [9,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One report recently found the clothing industry is already operating beyond all the planetary boundaries [ 52 ], with the exception of fresh water consumption [ 55 ]. The industry has also come under scrutiny in a number of countries for low wages, long working hours, and lapses in safe working conditions, including the 2013 collapse of a garment factory in Bangladesh that claimed over 1,000 workers’ lives [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%